Implementing the use of group discussion in writing descriptive text: A case on teaching method - Daulat Lumbangaol, Albert Welman; E. Silalahi, Dumaris; Herman, Herman (Journal of Education, Linguistics, Literature, and Art, 2024)
The purpose of this research to measure the effect of group discussion on the students’ ability in writing descriptive text at grade eight of SMP Negeri 9 Pematangsiantar. The research method of this research is the quantitative method using a quasi-experimental research design. In quasi-experiment design, there are two groups, the experimental and the control group, and for the test using pre-test and post-test. The population would be used in this study was all students of class VIII at SMP Negeri 9 Pematangsiantar. Based on the data analysis, it was found that the use group discussion method was effective in improving students’ ability in writing descriptive text. Mean pre-test in experimental class was 57,17 while the mean post-test was 71,20 mean pre-test in control class was 48,58 while the mean post-test was 64,37 standard deviation in experimental class was 2664 while in control class was 1950,75 mean post-test in experimental class control 71,20. 64,37 the hypothesis value showed that the t table value was higher than the t table value 2,34. 1673 the finding of the research indicate that the use of group discussion method was effective in students’ ability in writing descriptive text this is approved by the students score in experimental class is higher than the control class.